Bioekologi Udang Macrobrachium spp. di Sungai Banjaran Kabupaten Banyumas - Kusbiyanto Kusbiyanto (Fakultas Biologi | Universitas Jenderal Soedirman, 2009)
Shrimp species diversity in River Banjaran is in a trend to reduce from time to time. In order to verify this trend, a research on bioecology of freshwater shrimp Macrobrachium spp. In River Banjaran was done using survey method. River’s body was divided into three different areas according to their environmental condition. On each area, six sampling stations were defined with the distance among stations were ± 0.5 km. The shrimps were collected using electroshocker, ancho, and waring. The samples were preserved in 70% ethanol and were identified. Only four species of shrimps were found during the survey, those are Macrobrachium cowlesi, M. idea, M. esculentum, and M. oenone. Shrimp relative abundance among areas was similar with the highest relative abundance was found for M. cowlesi. Sex ratio analysis for all species showed that male individuals were more abundance than the female ones. This result provided a picture that species diversity of freshwater shrimps in River Banjaran is still in continuous decrease. Therefore, it is necessary to make some efforts to conserve the rest of Machrobrachium species in Banjaran River.